2008
DOI: 10.1021/ic800053e
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Field Photolysis of [Mo(CN)8]4− in Aqueous Hydrazine: Trapped Mo(II) Intermediate and Catalytic Disproportionation of Hydrazine by Cyano-Ligated Mo(III,IV) Complexes

Abstract: The substitutional photolysis of K4[Mo(CN)8].2H2O in 98% N2H4.H2O has been investigated in detail. A molybdenum(II) intermediate, K5[Mo(CN)7].N2H4, is isolated in the primary stage of the reaction that involves the oxidation of N2H4 to N2, as evidenced by the analysis of evolving gases. The powder X-ray crystal structure of K5[Mo(CN)7].N2H4 indicates the pentagonal bipiramidal geometry of the anion and the presence of N2H4 in proximity to the CN(-) ligands. The salt is characterized by means of EDS, IR, UV-vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Although hydrazine seems like a more reasonable product from symmetric protonation in some cases metal complexes have been shown to catalyse the disproportionation of hydrazine into ammonia and dinitrogen. 65 As described above, it is believed that Schrock's tris(amido)amine molybdenum catalyst for the conversion of dinitrogen into ammonia follows an asymmetric Chatt type pathway. 4,14,66 In the Leigh system a Chatt type mechanism seems unlikely; such a mechanism would involve iron(0) which generally functions as a two electron reductant performing one electron chemistry.…”
Section: Potential Mechanisms For Ammonia and Hydrazine Formationmentioning
confidence: 99%
“…Although hydrazine seems like a more reasonable product from symmetric protonation in some cases metal complexes have been shown to catalyse the disproportionation of hydrazine into ammonia and dinitrogen. 65 As described above, it is believed that Schrock's tris(amido)amine molybdenum catalyst for the conversion of dinitrogen into ammonia follows an asymmetric Chatt type pathway. 4,14,66 In the Leigh system a Chatt type mechanism seems unlikely; such a mechanism would involve iron(0) which generally functions as a two electron reductant performing one electron chemistry.…”
Section: Potential Mechanisms For Ammonia and Hydrazine Formationmentioning
confidence: 99%
“…Moreover,e ven if the photochemistry of the [Mo IV (CN) 8 ] 4À is well-documented, all of the known photoproducts are diamagnetic. [20] To the best of our knowledge,w eh ave isolated the first paramagnetic photoproduct. This result opens very interesting perspectives in molecular magnetism for the photochemical preparation of new anisotropic building blocks.…”
mentioning
confidence: 99%
“…The complexes with half-unit Schiff bases containing pendant amine groups were particularly interesting for us since they could further be used as building blocks for extended systems. On the other hand, working with molybdenum and tungsten complexes, we have recently observed that several M(IV) cyano complexes participate in redox processes involving and influencing the reactivity of various ligands (O 2 , NO, nitriles, hydrazine) [9][10][11][12][13][14]. The propensity of these metals for both redox as well as template organic reactions prompted us to further study their reactivity towards potential Schiff-base components.…”
mentioning
confidence: 99%